Exploring the G.E.A.R.S. of learning for youth through community development - Meng, Lee Kwan; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2022)
Learning leads to development and change for youth. It is through learning that the youth acquire knowledge, skills, values, and worldview that effect change that is based on the asset or strength-based youth development model. Such learning develops from their informal and nonformal learning that involves skill building, exploration, reflection, creativity, role experimentation from their leisure and play opportunities. Informal and nonformal learning take place from supervised Out-of-School (OST) programs where the young people develop various social skills. This paper examines the literature and theories related to OST settings, social learning, youth development, and how youth learn within a community. The youths referred here are those from Generation Z who were born between 1995 and 2010 or the late Millennials. Not all the youths’ time in school are in the formal learning settings. Part of it is in the OST settings such as extracurricular activities of their school activities or in recreational pursuits for those not in the school system such as those in sports, recreational, or youth-serving organizations. Studies have found that OST programmes contribute to academic outcomes, social/emotional outcomes, prevention outcomes, and health and wellness outcomes, as well as developmental benefits where one of one of its programme elements is active forms of learning to enable youths to learn skills. Theoretically, OST relates to Vygotsky’s (1978) sociocultural activity theory (AT). Since youth is a transition from childhood to adulthood, likewise, so is their learning, that is, low pedagogy/high andragogy. Together with a study on Gen Z learning and that of Bandura’s social cognitive/social learning theories, a new model of youth learning was conceptualized for community of practice. This model is G.E.A.R.S – Guided, Experiential, Activity-oriented, Reflection, and Self-understanding. This model is a form of nonformal learning that is practical, holistic, and real world that complements formal classroom learning.